Characteristic and evaluation of sustainability artisanal bonito (Auxis spp.) fisheries in the Prigi Bay and surrounding waters - Wujdi Arief; Setyadji Bram; Hartaty Hety; Sulistyaningsih Ririk Kartika (E3S Web of Conferences, 2021)
Bonito plays an important role as the main ingredient for marinated products and provides a livelihood for coastal communities. Given the emergence of Indonesia's over-exploited small-scale marine fisheries resources, this study aims to characterize and evaluate fishery’s sustainability based on bioeconomic analyses. Time series catch and effort data were collected from 2005 to 2019 provided by Archipelagic Fishing Port of Prigi. Five surplus production models were also employed to generate catch-and-effort-based biological parameters, namely intrinsic growth rate (r), catchability (q), and carrying capacity (K). By adding economy parameters such as cost and price, the sustainability of catch and effort was also estimated at three management conditions. The catch abundance was peaked in April and September, characterized by the lack of rain. The CPUE was varied inter-annually. However, it declined during the last decade, indicating that the stock size was decreased. Although the average catches from 2015-2019 (9,984 tons) are lower than CMSY (11,695 tons). However, the effort in 2019 (15,239 trips) has exceeded EMEY (14,237 trips). Hence, reducing fishing efforts or maintaining it at E2018 level was suggested as a precaution to keep the fishery’s sustainability and simultaneously generate optimum profit.